The power of constant prayer and communion with God - Jeynes, William (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
"Billions of people in the world want a sound basis for improving the amount of fulfillment and personal success in their lives. Over the years, many have lauded the importance of prayer in one's life. To whatever degree that is true, how much more is constant prayer even more powerful than Sunday or Saturday prayer or even daily prayer. Communing with God throughout the day is one of the most underestimated means of experiencing peace and joy in one's life, as well as having God's love flow from one's heart and lips. Countless numbers of people around the world pray in order to have some of the key advantages in personal serenity, purpose, and insight that will enable them to have the edge in life necessary in order to have victory and fulfillment. How much more will constant prayer and communion with God enable people to have a permant advantage and edge. This book examines how the practice of constant prayer and communion with God can fill a person with more love, joy, peace, self-discpline, faith, direction in life, humility, sensitivity to God, consistency, and purpose. It is intellectually stimulating, but immensely practical. By applying the many principles shared in this book, it can literally change your life and make you stronger in virtually every area of your life"--